A cor e a espacialidade nas pinturas de Santhiago Selon - Sampaio, Glayson Arcanjo de (2014)
This paper is about the process of creation of brazilian artist Santhiago Selon, addressing the geometric universe proposed by the artist in the exhibition “New Horizon” occurred in 2012 and paintings done on walls and other urban spaces in the city of Goiânia, Brazil. Analyzes preparatory drawings, discusses the surface and how the artist make